Impact Of Service Marketing On Student Decisions - Onsardi, Onsardi; Wulandari , Kiki; Finthariasari , Meilaty; Yulinda , Ade Tiara (Universitas Muhammadiyah Sidoarjo, 2021)
This research aims to determine the impact of service marketing on student decision-making to decide on the choice of the Faculty of Economics and Business of Muhammadiyah University of Bangkulu. This study uses quantitative methods. In this study, the population was all students of the School of Economics and Business of Muhammadiyah Bengkulu University, a total of 1,606 people, and 161 respondents were selected as a sample. The sampling technique uses proportional random sampling. Use questionnaires to collect data. Multiple linear regression is used as a way to analyze data. The conclusion of the research results proves that service marketing has had an impact on students' decision to choose the Faculty of Economics and Business of Muhammadiyah University. Product factors have a positive and significant effect on student decisions. This price factor in the form of SPP has a negative effect. Promotion factors have a positive and significant effect. Location factors are positive and significant. HR factors have a positive and significant effect. Meanwhile, process factors have no effect on student decision. The physical evidence factor has a positive and significant effect on student decisions to choose the Faculty of Economics and Business, Muhammadiyah University of Bengkulu.